The Effect of Entrepreneurship Orientation and Market Orientation on Msme Performance in Bandung City in West Java - Rani Eka Arini (The Es Economics and Entrepreneurship, 2022)
Performance can be interpreted as an achievement obtained from certain work results. Every organization that carries out business activities will expect to always get the best performance results even though the global situation will always fluctuate. MSMEs as organizations that carry out business activities will also have the hope of having good and increasing performance so that the goals of MSMEs will be achieved. This writing uses a quantitative research approach. The focus of the research is orientation and market orientation on the performance of MSMEs. This research was conducted in Bandung in West Java, Bengkulu. Based on the discussion, 1) entrepreneurial orientation has a positive and significant effect on the performance of MSMEs, 2) market orientation has a positive and significant effect on the performance of MSMEs, and 3) entrepreneurial orientation and market orientation simultaneously influence the performance of SMEs. The suggestions and recommendations to related parties are for MSMEs in Bandung City. In West Java, it is expected to be able to improve market orientation and orientation to improve MSME performance.